The prevalence of actual medication error 2019-2022 in the online medication error reporting system (mers) and its associated factors in Kelantan - Raes, Rizq Fazzali Abdul (2023)
Background: The online Medication Error Reporting System (MERS) is a voluntary reporting system of medication error (ME) in public and private healthcare facilities. Introduced in 2013, the online MERS includes the reporting of near miss and actual MEs. The prevalence of reported MEs was increasing and many factors were associated with MEs, however little is known about the prevalence of actual MEs and its associated factors in Kelantan. Objective: The study objectives were to determine the prevalence and factors associated with actual MEs in Kelantan from 2019 to 2022. Methodology: A retrospective secondary data record review was conducted on ME reports from 2019 to 2022 in Kelantan obtained from the online MERS database. Data was analysed using simple and multiple logistic regression for endorsed MEs report. Results: A total of 15937 ME reports from the database were analysed. The prevalence of actual MEs in 2019 to 2022 in Kelantan was 1.6%, which ranged from 1.1% to 2.8% yearly from 2019 to 2022. Six independent variables were significantly associated with actual MEs which include inexperienced personnel (AdjOR 1.84; 95% CI: 1.36 to 2.48), sound-alike medication (AdjOR 1.71; 95% CI: 1.12 to 2.62), look-alike packaging (AdjOR 3.65; 95% CI: 2.03 to 6.57), stock arrangements/ storage problems (AdjOR 6.72; 95% CI: 3.87 to 11.68), failure to adhere to work procedure (AdjOR 10.59; 95% CI: 7.60 to 14.75), and wrong labeling/ instruction on dispensing envelope or bottle/ container (AdjOR 4.17; 95% CI: 1.89 to 9.23). Conclusion: Even with the increasing number of MEs and near misses reported every year, the prevalence of actual MEs is reducing in Kelantan, further research is warranted to investigate such occurrence as it may imply under reporting. Increasing near misses may also eventually lead to actual MEs. Awareness program and trainings are required to increase reporting of errors by strengthening the medication safety programme and cultivate safety cultures in medication management for prevention of MEs.